Optimising the business of red onion farmers through effective management and innovation of processing technologies - Nanik Hariyana; Nurhadi Nurhadi; Hesty Prima Rini; Arief Budiman (Journal of Community Service and Empowerment)
This community service journal is entitled Optimizing shallot farmers' efforts through effective management and processing technology innovation which examines methods to increase the profitability of shallot farmers through efficient management techniques and advanced processing innovations. Significant economic activities in several areas, such as Kedung Dalem Village, Dringu District, Probolinggo Regency, are extensive cultivation. This study examines the problems currently faced by farmers, such as market volatility and post-harvest losses, and suggests solutions that are largely focused on improving management practices and implementing advanced processing technologies. It is hoped that by improving managerial skills and using advanced processing techniques, shallot cultivation in the target community will become more productive, less vulnerable to losses, and ultimately more economically sustainable. The method used is a qualitative method with information interviews with informants. The results of the study emphasize the importance of combining advanced technology with efficient management techniques to improve the economic development of rural communities and agricultural sustainability.